Study on the effectiveness of in-situ high intensity ultrasonic (HIU) in increasing the rate of filtration in palm oil industries. - Ahmad, Ziad Sulaiman; Rosli, Mohd Yunus; Radzuan, Junin; Hathaichanok, Duriyanbunleng (Penerbit Universiti Sains Malaysia, 2004)
Palm oil industry has been the bread and butter of Malaysian industry ever since palm tree was brought into the country in the 1960’s. The fast growth of this industry has made Malaysia to be the largest producer of palm oil for many years. Palm tree is easily grown in tropical climate countries. Hence, the profitable industry has been adopted by neighboring countries such as Thailand, Indonesia, Vietnam, Cambodia, as well as Philippines. Realizing the competitiveness of the industry and the advantages of neighboring countries with large cultivating land, much research has been focused on improving the overall operation of the industry so as to increase its productivity.